Fossilized Versus Improved Errors in Eighth Grade Students’ Instagram Recount Text: Solutions and Teaching Strategies - Nisa, Ana Khoirun; Afifi, Nur (Jurnal Bahasa Inggris Terapan, 2024)
In the era of technological advancement, generation Z, especially those who are accustomed to using Instagram, is significantly affected by the development of social media. This research focused on efforts to carefully identify dominant errors in students' text recount writing, especially in the caption section on the Instagram platform, as well as offer solutions to overcome their difficulties in writing this type of text. The method that used is a qualitative descriptive method where researchers give writing tasks to students to analyze and identify errors in their writing. In addition, interviews were conducted with two English teachers to get effective solutions in overcoming students' difficulties. In analyzing the data, the researchers refer to Brown's theory of misclassification, such as misformation, addition, omission, and misordering, which are then categorized into fossilized error and improved error. The results of the analysis showed that students tended to make misformation mistakes dominantly. Teachers provide solutions by repeating material until understanding is achieved, giving repeated exercises, and providing evaluations of students' writing, in the hope that the evaluation process can correct errors in their writing, The evaluation process can correct errors in their writing. It is expected that students will not only correct their mistakes but can also improve overall writing skills, creating a more meaningful learning experience.